Bionanocomposites from electrospun PVA/pineapple nanofibers/Stryphnodendron adstringens bark extract for medical applications - Costa, Ligia Maria Manzine; de Olyveira, Gabriel Molina; Cherian, Bibin Mathew [UNESP]; Leão, Alcides Lopes [UNESP]; de Souza, Sivoney Ferreira; Ferreira, Mariselma (Elsevier, 2013)
Tissue engineering has been defined as an interdisciplinary field that applies the principles of engineering and life sciences for the development of biological substitutes to restore, maintain or improve tissue function. This area is always looking for new classes of degradable biopolymers that are biocompatible and whose activities are controllable and specific, more likely to be used as cell scaffolds, or in vitro tissue reconstruction. In this paper, we developed a novel bionanocomposite with homogeneous porous distribution and prospective natural antimicrobial properties by electrospinning technique using Stryphodedron barbatimao extract (Barbatimão). SEM images showed equally distribution of nanofibres. DSC and TGA showed higher thermal properties and change crystallinity of the developed bionanocomposite mainly because these structural modification. © 2012 Elsevier B.V.
Keywords: Bionanocomposite; Electrospinning; Medical applications; Natural nanocomposite; Antimicrobial property; Bark extracts; Bio-nanocomposite; Bionanocomposites; Cell scaffold; Crystallinities; DSC and TGA; Electrospinning techniques; Electrospuns; In-vitro; Interdisciplinary fields; Life-sciences; SEM image; Structural modifications; Tissue function; Tissue reconstruction; Biopolymers; Tissue; Scaffolds (biology); antimicrobial activity; bark; biodegradation; composite; legume; medicinal plant; nanotechnology; plant extract